Trade liberalization and comparative advantage: Evidence from Indonesia and Asian trade partners - Rudi Purwono; Lilik Sugiharti; Rossanto Dwi Handoyo; Miguel Angel Esquivias Padilla (Economies, 2022)
This study analyzes whether ongoing liberalization has resulted in more profound trade expansion for Indonesia versus regional partner countries. A gravity model is first employed to find whether regional trade agreements resulted in more significant intra-regional exports or diverted trade. This study applies the generalized method of moment (GMM-sys) and the Poisson pseudo-maximum likelihood (PPML) estimator. Four groups of manufactured products are aggregated according to technology intensity, and two nature-based groups of products are estimated in the dynamic panel model. Additionally, revealed comparative advantage (RCA) and a trade balance index (TBI) for 5120 products are used to map goods based on specialization-advantage patterns. The gravity model indicates that regional trade agreements supported trade in manufactured and naturally sourced goods but not in high-tech and primary goods. Additionally, export expansion took place in goods that revealed comparative advantage and export specialization. Competition has increased between Indonesia and four regional trade partners: China, India, Thailand, and Vietnam. Indonesia gained from trading primary materials while losing in some low-cost manufacturing sectors. The potential for trade expansion remains large, as trade patterns differ among regional partners.
Keywords: 330; ASEAN; free trade agreements; gravity equation; Indonesia; products mapping; regional integration; regionalism; revealed comparative advantage; trade balance; trade creation; trade liberalization